The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1037/abn0000061
|View full text |Cite
|
Sign up to set email alerts
|

The temporal “pulse” of drinking: Tracking 5 years of binge drinking in emerging adults.

Abstract: Binge drinking is associated with clinically significant individual-level and public health consequences. The topography of binge drinking may influence the emergence of consequences but studies of topography require a higher level of temporal resolution than is typically available in epidemiological research. To address topography across the five “peak” years of binge drinking (18 to 23 years), we assessed daily binge drinking via successive 90-day Timeline Follow back interviews of 645 young adults (resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
(64 reference statements)
1
37
0
Order By: Relevance
“…This pattern has been shown across samples, with the overwhelming majority focusing on college students (Del Boca et al, 2004; Hoeppner et al, 2012; Labhart & Kuntsche, 2014; Maggs et al, 2011; Tremblay et al, 2010; Wood et al, 2007), but also has been demonstrated in the general population (Kushnir & Cunningham, 2014). The current findings are consistent with Goldman et al (2011), which showed weekly patterns of drinking escalation from weekday to weekend, and congruous with the results of Reich et al (2015), which revealed that those choosing to binge drink varied by day of the week, with rates peaking on Saturdays.…”
Section: Discussionsupporting
confidence: 89%
“…This pattern has been shown across samples, with the overwhelming majority focusing on college students (Del Boca et al, 2004; Hoeppner et al, 2012; Labhart & Kuntsche, 2014; Maggs et al, 2011; Tremblay et al, 2010; Wood et al, 2007), but also has been demonstrated in the general population (Kushnir & Cunningham, 2014). The current findings are consistent with Goldman et al (2011), which showed weekly patterns of drinking escalation from weekday to weekend, and congruous with the results of Reich et al (2015), which revealed that those choosing to binge drink varied by day of the week, with rates peaking on Saturdays.…”
Section: Discussionsupporting
confidence: 89%
“…These findings add credence to the notion that animals crossing the threshold for binge drinking (≥80 mg/dl), may require several days for recovery before consuming large amounts of EtOH again, whereas the animals consuming the Boost ® solution alone are not subject to such constraints and can maintain more consistent intakes across the 14 days of access. Although not used in the formal definition of binge use, binge‐like consumption in adolescents typically follows a pattern of high levels of drinking followed by days of little consumption (e.g., binge drinking on weekends) (Reich et al., ). It is interesting that the intake of our animals showed a similar variable pattern under circumstances when free access was given daily, suggesting that the variability in binge pattern of use over day in human adolescents may not merely be opportunistic, but could reflect in part acute withdrawal and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in binge drinking days are likely to be associated with corresponding increases in other risks (58). In addition to the obvious immediate effects of consuming a large amount of alcohol at a single sitting, there is evidence to suggest that more adverse events are associated with 2 or more days of binge (heavy) drinking a week than with more regular consumption of smaller amounts of alcohol (64). …”
Section: Discussionmentioning
confidence: 99%